Single Amino Acid Residue W33 of tva Receptor Is Critical for Viral Entry and High-Affinity Binding of Avian Leukosis Virus Subgroup K - Gáliková, Eliška; Přikryl, David; Prost, Salomé; Kučerová, Dana; Trejbalová, Kateřina; Hejnar, Jiří (Viruses, 2025)
Avian leukosis virus (ALV), the prototypical alpharetrovirus, causes tumorigenesis, immunosuppression, and wasting disease in poultry. The ALV genus is classified into ten subgroups, which differ in their host range, cell tropism, and receptor usage. The subgroups A, B, K, and J cause significant economic losses worldwide. The most recently discovered subgroup, ALV-K, which is now widespread in China, has been shown to use the tva cell receptor and share it with ALV-A. However, the specific amino acid residues crucial for ALV-K host cell entry remain unknown. Using precise tva expression and chimeric tva receptors, we further elucidated the significance of the cysteine-rich domain in mediating interactions with both ALV-A and ALV-K. Through a comprehensive analysis of mutated tva receptor variants, we pinpointed tryptophan at position 33 (W33) as a pivotal amino acid residue essential for ALV-K virus binding and entry. Of note is the finding that the substitution of W33 induced resistance to ALV-K while preserving sensitivity to ALV-A. This study not only represents an advance in the understanding of the specificity of the tva receptor for ALV-K, but also offers a biotechnological strategy for the prevention of ALV-K infections in poultry.
Keywords: kur domácí; Poultry Diseases; Virus Internalization; Virus Attachment; Receptors, Virus; Cell Line; virus ptačí leukózy; ptačí proteiny; Chickens; Avian Leukosis Virus; Avian Proteins; guineafowl; tva receptor; internalizace viru; avian leukosis virus; chicken; virové receptory; ptačí leukóza; Amino Acid Substitution; nemoci drůbeže; Avian Leukosis; Animals; zvířata; substituce aminokyselin; buněčné linie; přichycení viru